2020
DOI: 10.1155/2020/8831694
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Potential, Iron and Zinc Bioaccessibility, and Sensory Quality of Uapaca kirkiana Fruit Jam Fermented with Lactobacillus rhamnosus Yoba

Abstract: Uapaca kirkiana is an underutilised indigenous fruit tree (IFT) found in the miombo ecological zone in sub-Saharan Africa. Furthermore, sub-Saharan Africa is home to many nutritionally insecure people who suffer from micronutrient deficiency. The incorporation of probiotic strains in jams as a possible way of enhancing mineral accessibility, food quality, and health is limited in Africa. This study monitored the probiotic potential, bioaccessible iron and zinc, and organoleptic properties of U. kirkiana fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…is study noted a decrease in the final pH and an increase in the TA of the cowpea-peanut milk samples as the fermentation progressed. is could be ascribed to be the action of Lacticaseibacillus rhamnosus Yoba as it breaks down sugars into lactic acid [7]. A similar trend was also observed in the fermented cow milk (control).…”
Section: Ph and Total Aciditysupporting
confidence: 61%
See 2 more Smart Citations
“…is study noted a decrease in the final pH and an increase in the TA of the cowpea-peanut milk samples as the fermentation progressed. is could be ascribed to be the action of Lacticaseibacillus rhamnosus Yoba as it breaks down sugars into lactic acid [7]. A similar trend was also observed in the fermented cow milk (control).…”
Section: Ph and Total Aciditysupporting
confidence: 61%
“…e trypsin inhibitor and phytic acid content in fermented cowpea-peanut milk were very low after fermentation (Table 3). is could be due to the beneficial action of the probiotic microorganism in removing the antinutritive compounds that promote protein crosslinking (phenolic and tannin compounds) and inhibit digestive enzymes (trypsin and chymotrypsin inhibitors) from food material and production of microbial proteases, which could degrade and release some of the proteins from the matrix during fermentation [7,46]. Also, the use of NaHCO 3 during soaking might have reduced the trypsin inhibitor and phytic acid content.…”
Section: Mineral and Antinutritional Composition Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Uapaca kirkiana produces nutritious fruits with many foods and non-food uses due to its phytochemical content [83,104], making it important to address malnutrition. A recent analytical study in support of traditional knowledge found that U. kirkiana fruit is a good source of micronutrients (Fe, Cu, Zn), phenolic compounds, vitamin C and bioactive compounds [497][498][499]. Therefore, it is recommended that these functional tree foods be incorporated into diets for their nutritional and health benefits, such as additives and as probiotic jams, especially for women and children in sub-Saharan Africa.…”
Section: Nutritional Value Of Non-timber Forest Productsmentioning
confidence: 99%
“…In addition, a study to determine the effect of harvesting time on physicochemical properties and selected nutritional composition of V. infausta fruits found that the best harvest time was January, when fruits were most attractive to consumers; however, further work is required on the physicochemical properties and nutritional value [494]. However, some processing technologies have been developed to add value in quality, mineral bioaccessibility, shelf-life and postharvest handling to IFT fruits [497].…”
Section: Post-harvest Issuesmentioning
confidence: 99%